Simulated games activity vs continuous running exercise: A novel comparison of the glycemic and metabolic responses in T1DM patients. Issue 2 (4th March 2014) - Campbell, M. D.; West, D. J.; Bain, S. C.; Kingsley, M. I. C.; Foley, P.; Kilduff, L.; Turner, D.; Gray, B.; Stephens, J. W.; Bracken, R. M.
Abstract : To compare the glycemic and metabolic responses to simulated intermittent games activity and continuous running exercise in type 1 diabetes. Nine patients (seven male, two female; 35 ± 4 years; HbA1c 8.1 ± 0.2%/65 ± 2 mmol/mol) treated on a basal‐bolus regimen completed two main trials, a continuous treadmill run (CON) or an intermittent running protocol (INT). Patients arrived to the laboratory fasted at ∼ 08:00 h, replicating their usual pre‐exercise meal and administering a 50% reduced dose of rapid‐acting insulin before exercising. Blood glucose (BG), K +, Na ++, pH, triglycerides, serum cortisol and NEFA were measured at baseline and for 60 min post‐exercise. Interstitial glucose was measured for a further 23 h under free‐living conditions. Following exercise, BG declined under both conditions but was less under INT (INT −1.1 ± 1.4 vs CON −5.3 ± 0.4 mmol/L, P  = 0.037), meaning more patients experienced hypoglycemia (BG ≤ 3.5 mmol/L; CON  n  = 3 vs INT  n  = 2) but less hyperglycemia (BG ≥ 10.9 mmol/L; CON  n  = 0 vs INT  n  = 6) under CON. Blood lactate was significantly greater, and pH lower, with a temporal delay in K + under INT ( P  < 0.05). No conditional differences were observed in other measures during this time, or in interstitial glucose concentrations during the remaining 23 h after exercise. Simulated games activity carries a lower risk of early, but not late‐onset hypoglycemia than continuous running exercise in type 1 diabetes.